Main Directions of Modernization of Services in Uzbekistan - Sattarov, Sattarov (Universitas Muhammadiyah Sidoarjo, 2022)
The essence of the notion of modernization and the specifics of service sector modernization are described in this article. The essential directions for Uzbekistan's service sector modernization are also proposed